Globalizacja w nauczaniu Jana Pawła II - GAŁKOWSKI, Jerzy W.; STANNY, Dominik (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
The objective of the article is to explore John Paul II’s attitude to the processes of globalization. While the Pope did not directly focus on the phenomenon of globalization as such, he referred to it in two of his addresses to the members of the Pontifical Academy of Social Sciences. On many other occasions though, John Paul II considered the problems related to globalization, in particular the issue of economic freedom, which, however, he would not associate specifically with globalization. Thus the authors attempt to reconstruct John Paul II’s attitude to globalization by means of an analysis of these aspects of his teaching which, in their opinion, prove significant in this field. John Paul II considered globalization an immediate result of the downfall of the communist system and perceived it, above all, in terms of broader circulation of people, capital and goods. He saw numerous positive sides of globalization and free market, in particular due to their efficiency in meeting human needs, generat− Abstracts 352 ing material welfare and engendering independence, self−reliance and free initiative in individuals. However, the Pope’s positive approach to globalization was accompanied by his insight into the potentially negative phenomena it may involve, such as strengthening social inequalities or devastation of the environment. While pointing to the threats globalization can pose, the Pope stressed that, as a phenomenon as such, it must not be considered a priori as good or bad. It will become either good or bad, depending on how human beings will shape it. John Paul II’s opinion on globalization has its ultimate justification in his anthropological views, in which he stressed the primacy of the human person over objects or utalitarian values. Translated by Dorota Chabrajska